Towards sustainable biointelligent food design: structuring potential of plant-based materials exemplified using apricot seed oil oleogels and bigels through 3D food printing - Reinmuth, Evelyn; Fahmy, Ahmed Raouf; Ribette, Olivia; Jekle, Mario (Frontiers in Sustainable Food Systems, 2025)
Background/IntroductionBiointelligence in the approach of food additive manufacturing represents a significant advancement, enabling the reverse engineering and design of foods. Legislation restricting trans-fats has accelerated research into alternatives, but ingredients like saturated and trans fats play key roles in food quality and functionality. Oleogels are a promising replacement. Food additive manufacturing introduces a biointelligent approach, combining biological and technical components with information technology to optimize food design. This study investigates 3D printing of oleogel and bigel systems using apricot seed oil, aiming to assess their significance, applicability, and printability as sustainable alternatives to trans fats for innovative, resource-efficient food production.MethodsApricot seed oil, rich in antioxidants and polyunsaturated fatty acids, was processed into plant-based oleogels and bigels. The material systems were incorporated into 3D printed food structures. Material characterization and techno-functional analysis were conducted to evaluate the suitability of apricot seed oil for structuring 3D printed foods and controlling food texture.ResultsAdjusting the type and concentration of oil-gelator mixtures enabled tailored texture and lipid distribution to fit consumer preferences. Sustainability impacts were assessed at intermediate processing steps, demonstrating the value of holistic evaluations beyond technical factors.DiscussionBiointelligent 3D printing offers a platform to optimize sensory and sustainability qualities in food design. The integration of apricot seed oil into novel food matrices enables versatile nutritional product development, supporting researchers and industry stakeholders in advancing consumer-centric, sustainable production and consumption practices.